A closer look at alcohol‐induced changes in the ghrelin system: novel insights from preclinical and clinical data. (27th April 2021) - Deschaine, Sara L.; Farokhnia, Mehdi; Gregory‐Flores, Adriana; Zallar, Lia J.; You, Zhi‐Bing; Sun, Hui; Harvey, Deon M.; Marchette, Renata C. N.; Tunstall, Brendan J.; Mani, Bharath K.; Moose, Jacob E.; Lee, Mary R.; et al.
Abstract: Ghrelin is a gastric‐derived peptide hormone with demonstrated impact on alcohol intake and craving, but the reverse side of this bidirectional link, that is, the effects of alcohol on the ghrelin system, remains to be fully established. To further characterize this relationship, we examined (1) ghrelin levels via secondary analysis of human laboratory alcohol administration experiments with heavy‐drinking participants; (2) expression of ghrelin, ghrelin receptor, and ghrelin‐O‐acyltransferase (GOAT) genes ( GHRL, GHSR, and MBOAT4, respectively) in post‐mortem brain tissue from individuals with alcohol use disorder (AUD) versus controls; (3) ghrelin levels in Ghsr knockout and wild‐type rats following intraperitoneal (i.p.) alcohol administration; (4) effect of alcohol on ghrelin secretion from gastric mucosa cells ex vivo and GOAT enzymatic activity in vitro ; and (5) ghrelin levels in rats following i.p. alcohol administration versus a calorically equivalent non‐alcoholic sucrose solution. Acyl‐ and total‐ghrelin levels decreased following acute alcohol administration in humans, but AUD was not associated with changes in central expression of ghrelin system genes in post‐mortem tissue. In rats, alcohol decreased acyl‐ghrelin, but not des‐acyl‐ghrelin, in both Ghsr knockout and wild‐type rats. No dose‐dependent effects of alcohol were observed on acyl‐ghrelin secretion from gastric mucosa cells or on GOAT acylation activity. Lastly, alcohol and sucrose produced distinct effects on ghrelin in rats despite equivalent caloric value. Our findings suggest that alcohol acutely decreases peripheral ghrelin concentrations in vivo, but not in proportion to alcohol's caloric value or through direct interaction with ghrelin‐secreting gastric mucosal cells, the ghrelin receptor, or the GOAT enzyme. Abstract : Alcohol suppresses plasma ghrelin in humans and rats in vivo, an effect that does not appear to be merely due to its caloric value. Alcohol does not suppress GOAT acylation activity in vitro or gastric mucosal cell secretion of acyl‐ghrelin ex vivo. Future work is needed to shed light on the exact mechanisms of how alcohol affects ghrelin.